Scrap Reduction By Using Total Quality Management Tools - Kumar, Sanjay; Mantha, S.S; Kumar, Arun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> 0 false 18 pt 18 pt 0 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-font-family:"Times New Roman";} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.25in 1.0in 1.25in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]--> <!--StartFragment--> A case study was carried out in one of the leading Indian industries manufacturing pre-stressed concrete steel strands (PC wire). It has major applications in bridges and construction industry. During study, lot of scrap was observed. Reasons for scrap was found out by using total quality management tools (TQM). Such as brainstorming, cause & effect diagram and pareto analysis. Main reasons were left over rings, non-conformity, chheda and weld/wire breakage. In the present study, scraps due to left over rings were reduced gradually by taking suitable action. <!--EndFragment-->